An obligatory role of NF-κB in mediating bone marrow derived endothelial progenitor cell recruitment and proliferation following endotoxemic multiple organ injury in mice. - Sun-Zhong Mao; Xiaobing Ye; Gang Liu; Dongmei Song; Shu Fang Liu (PLoS ONE, 2014)
Recruitment of bone marrow derived endothelial progenitor cells (BMDEPCs) alleviates multiple organ injury (MOI) and improves outcomes. However, mechanisms mediating BMDEPC recruitment following septic MOI remain largely unknown. This study characterized the kinetics of BMDEPC recruitment and proliferation and defined the role of NF-κB in regulating BMDEPC recruitment and proliferation.Chimeric mice with an intact or disrupted NF-κB p50 gene and BMDEPC-restricted expression of green fluorescent protein were created and injected with LPS (2 mg/kg, i.p.). BMDEPC recruitment and proliferation in multiple organs were quantified. BMDEPC recruitment and proliferation are highly organ-dependent. Lungs had the highest number of BMDEPC recruitment, whereas heart, liver and kidney had only a small fraction of the number of BMDEPCs in lungs. Number of proliferating BMDEPCs was several-fold higher in lungs than in other 3 organs. Kinetically, BMDEPC recruitment into different organs showed different time course profiles. NF-κB plays obligatory roles in mediating BMDEPC recruitment and proliferation. Universal deletion of NF-κB p50 gene inhibited LPS-induced BMDEPC recruitment and proliferation by 95% and 69% in heart. However, the contribution of NF-κB to these regulations varies significantly between organs. In liver, universal p50 gene deletion reduced LPS-induced BMDEPC recruitment and proliferation only by 49% and 35%. NF-κB activities in different tissue compartments play distinct roles. Selective p50 gene deletion either in stromal/parenchymal cells or in BM/blood cells inhibited BMDEPC recruitment by a similar extent. However, selective p50 gene deletion in BM/blood cells inhibited, but in stromal/parenchymal cells augmented BMDEPC proliferation.BMDEPC recruitment and proliferation display different kinetics in different organs following endotoxemic MOI. NF-κB plays obligatory and organ-dependent roles in regulating BMDEPC recruitment and proliferation. NF-κB activities in different tissue compartments play distinct roles in regulating BMDEPC proliferation.